Application of the Project Based Learning Model in Improving English Learning Outcomes Simple Resent Tense Material in Class VIII-2 MTSn Samarinda Semester 2 Academic Year 2021/2022 - Ghozali, Imam (Educationist: Journal of Educational and Cultural Studies, 2022)
The learning that was done by the teacher during cycle I and cycle II showed good performance. The teacher begins to apply a variety of teaching methods and techniques, the teacher tries to stimulate student activity and creativity, the teacher presents learning English integrally, the teacher does not only communicates about the completion of a subject matter but also pays more attention to students' mastery abilities. This can be seen in the aspect of suitability response of instructions. There was an increase in stage I with a score of 70 to 75 in stage II and 85 in stage III, there was also a significant change in the aspect of students' active role in learning activities which increased from 75 in stage I to 90 in stage II and 100 in stage III. This also influences aspects of student responses regarding the application of the project based learning approach with successive scores of 90, 95 and 100 in stage III.